A chip-sized piezoelectric receiver for low-frequency, near-field wireless power transfer: design, modeling and experimental validation. (1st March 2021) - Halim, Miah A; Rendon-Hernandez, Adrian A; Smith, Spencer E; Arnold, David P
Abstract: This work presents the design, modeling and characterization of a chip-sized piezoelectric receiver for low-frequency, near-field wireless power transmission. Utilizing a laser micro-machined titanium suspension, one NdFeB magnet, and two PZT-5A piezo-ceramic patches, the receiver operates at its torsion mode mechanical resonance. Two unimorph piezo-ceramic transducers are designed to maximize the power density of the receiver while maintaining a low mechanical resonant frequency for low-frequency electrodynamic wireless power transmission. An equivalent lumped-element circuit model is used to model the system performance. A prototype device is fabricated, assembled and tested, and the experimental results are compared with the system model. The 0.08 cm 3 device generates a maximum of 360 μ W average power at 1 cm distance from a transmitter coil operating at 724 Hz and below human head and torso exposure limits. This data corresponds to 4.2 mW cm −3 power density. Overall, this volume-efficient design offers a low-profile and compact footprint for potentially wirelessly charging wearable and bio-implantable devices.